Pengaruh Literasi Keuangan Dan Sikap Keuangan Terhadap Perilaku Keuangan Dengan Self-Efficacy Sebagai Variabel Mediasi - Putu Aristya Adi Wasita; Rai Gina Artaningrum; Sarita Vania Clarissa (Universitas Pendidikan Ganesha, 2022)
Financial literacy and financial attitudes during this pandemic are very useful in managing all financial income and expenses. This is reflected in the behavior of the person. The independent variables of this research are financial literacy and financial attitude. Financial behavior as the dependent variable and self-efficacy as a mediating variable. This study used 67 samples. The data that has been obtained will be analyzed using the partial least square method. The results of the study stated that each variable of financial literacy, financial attitude, and self-efficacy had a significant positive effect. Financial literacy and financial attitudes have a significant positive effect on self-efficacy. The self-efficacy variable as a parameter of financial literacy on financial behavior states that it partially mediates while the relationship between financial attitudes and behavior is fully mediated by self-efficacy